Organic Reactions 2011
DOI: 10.1002/0471264180.or003.03
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Ketenes and Ketene Dimers*Present address, M. W. Kellogg Co., 225 Broadway, New York, N. Y.

Abstract: Ketenes contain the functional group CCO. They have been classified as aldoketenes and ketoketenes. The ketenes are prepared by modifications of the general methods for the synthesis of olefins. The ketenes are much more reactive than simple olefins, however, and are more likely to enter into combination with the reagents from wich they are prepared or with solvents used or into self‐condensation to yield dimers or polymers, Many of the aldoketenes, which are generally more reactive than ketoketenes, have n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Vinylketenes are valuable synthetic intermediates, and have recently found new applications. Staudinger first suggested that they were formed by an intriguing electrocyclic pathway upon pyrolysis of carvone, as cited in 1912 (Scheme ),1a,22 but this has apparently never been replicated.…”
Section: Ketenes In Synthesismentioning
confidence: 99%
“…Vinylketenes are valuable synthetic intermediates, and have recently found new applications. Staudinger first suggested that they were formed by an intriguing electrocyclic pathway upon pyrolysis of carvone, as cited in 1912 (Scheme ),1a,22 but this has apparently never been replicated.…”
Section: Ketenes In Synthesismentioning
confidence: 99%
“…Exhaustive ketene preparation reviews have been published by several authors. [15][16][17][18][19][20][21][22][23][24][25] The polymerization of ketenes was investigated in the sixties and mainly for ketene [26,27] and dimethylketene. [22,[28][29][30][31][32] Both can be polymerized via cationic and anionic mechanisms by an appropriate choice of initiator Aldoketenes are well known to undergo fast dimerization and trimerization even at low temperatures but have never been polymerized so far.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most common methods used are zinc reduction of α-chloro acid chloride, Wolff rearrangement of α-diazo ketone and basedinduced hydrogen chloride elimination from an acid chloride [9][10][11] . Ring opening of cyclobutanones, 1,5-sigmatropic rearrangements of conjugated dienals, pyrolysis of esters, elimination from mixed anhydride and some special cases of photochemical fragmentation processes have been applied with excellent success [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%